Pemaafan Dan Aspek Kognitif Dari Stres Pada Mahasiswi Jurusan Kebidanan Tingkat Dua - Rahmandani, Amalia (Faculty of Psychology, Diponegoro University, 2015)
Forgiveness is considered as emotion-focused coping, whereas cognition is one aspect that is affected when someone is in a stressful situation. This study aims to examine the relationship between forgiveness with the cognitive aspect of stress. The subjects were 77 second degree students of midwifery. Data were collected using the Forgiveness Psychological Scale (43 item, Î± = .924) and Cognitive Aspect of Stress Scale (22 item, Î± = .886). The results showed a significant positive relationship between forgiveness with the cognitive aspect of stress (rxy = .504; p <.001). The higher the level of forgiveness, the better of cognitive activities in stressful situation, and conversely. Forgiveness contributed 25.4% to the prediction of cognitive aspect of stress